High temperature microwave absorbing properties of plasma sprayed La0.6Sr0.4FeO3-δ/MgAl2O4 composite ceramic coatings. Issue 5 (1st April 2020) - Jia, Hongyao; Zhou, Wancheng; Nan, Hanyi; Qing, Yuchang; Luo, Fa; Zhu, Dongmei
Abstract: Microwave absorbing materials (MAM) which can be used in high temperature and oxidation environments are strongly demanded in application, for conventional MAM fail due to various factors at high temperature. In this work, ceramic coatings composed of La0.6 Sr0.4 FeO3-δ and MgAl2 O4 have been successfully prepared via atmospheric plasma spraying and the microwave absorbing properties at high temperature are first reported. When the coatings of LSF/MAS matched with the metal substrate on thermal expansion, they can be treated repeatedly in the temperature range of 300 K–1173 K without peeling off. Meantime, the ceramic coatings with thickness of 1.5 mm showed considerable microwave absorption in the range of 8 GHz–18 GHz at high temperatures between 673 K–1173 K. The absorption bandwidth of LSF30 was 3.5 GHz for RL < −10 dB and 8 GHz for RL < −5 dB in the temperature range of 673 K–1173 K. LSF/MAS possesses the advantages of thin thickness and broad bandwidth at high temperatures, suggesting great potential as MAM in ultra-temperature environment.